P2-63. Functional connectivity from the dorso-lateral and medial parts of the parietal lobe: a cortico-cortical evoked potential study. Issue 9 (September 2017) - Togo, Masaya; Matsumoto, Riki; Takeyama, Hirofumi; Kobayashi, Katsuya; Shimotake, Akihiro; Usami, Kiyohide; Inouchi, Morito; Nakae, Takuro; Kunieda, Takeharu; Miyamoto, Susumu; Takahashi, Ryosuke; Ikeda, Akio
Abstract : The superior parietal lobule (SPL) and the medial parietal cortex are associated with integration of various kinds of information. Little is known about connections from the superior and medial parietal cortices in humans. Our objective is to delineate their connectivity by means of cortico-cortical evoked potential (CCEP). Subjects were eight patients who underwent chronic subdural electrode placement covering the dorso-lateral (SPL) or medial parietal cortices. Single-pulse electrical stimuli were delivered and CCEPs were obtained from the frontal and parietal areas by averaging electrocorticograms time-locked to stimuli. SPL stimulation elicited 75 CCEPs at the precuneus, precentral gyrus, the dorsal premotor area (dorsal PM). The precuneus elicited 66 CCEPs in the inferior parietal lobule (IPL), dorsal premotor area (PM) and SPL. The posterior cingulate cortex elicited 36 CCEPs at the middle cingulate cortex, SPL and the precuneus. This study demonstrated reciprocal connections between the superior and medial parietal cortices. While the precuneus tends to connect with the lateral frontal area, posterior cingulate cortex with medial frontal area. These findings would account for functional differentiation between these areas, and may help us understand seizure propagation in patients with parietal lobe epilepsy.